Allelopathic effect of the aqueous extract of Eucalyptus urophylla in corn and cowpea seeds (Research, Society and Development, 2020)
Eucalyptus is a plant species that has allelopathic properties, its leaves contain substances that prevent or reduce the germination of seeds of some species of plants. Therefore, the objective of this work was to evaluate the effect of the aqueous extract of fresh eucalyptus leaves (Eucalyptus urophylla) in different concentrations on the germination and initial development of corn seeds (Zea mays L.) and cowpea (Vigna unguiculata (L.) Walp). The variables analyzed were: germination percentage, germination speed index, seedling length, seedling fresh and dry matter mass. The aqueous extract of the fresh leaves of E. urophylla, show potentialities on the cowpea seeds, inhibiting the length and dry matter of seedling, which indicates the presence of possible allelopathic compounds. There were no significant differences for corn in any of the variables analyzed.